(3NWGHGJ GdCYeGd GdYedjI s - (3eMehO Cejf(B, (3Rhjds ((3GdEScfOQjI(B:s (3OGQ GdhaGA dOfjG GdWHGYI hGdfTQ(B,s, 2000)
(3cJGHI QSGdI GdCYeGd,NUGFU QSGdI GdCYeGd GdLjOI hYfhfI GdeXGQja,GdHQjO GdhGQO hGdHQjO GdUGOQ, GdeQGSdGJ GdOGNdjI,GdNUe,GdahGJjQ,GdNWGHGJ GdeQabIs
Keywords: (3EOGQIs; (3cJGHI QSGdI GdCYeGd(B((3cJGHI GdJbGQjQ(B)s